MEDIA EDUCATION AS A FACTOR OF INFORMATION SECURITY IN UKRAINE - Lutskyi, Maksym (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The aim of the article is to study individual aspects of the implementation of media education in the state in the context of ensuring information security of Ukraine. Research methods: documentary analysis, generalization from the field of media education organization, information from the field of creating information and communication technologies, as well as information protection practices and countering propagandistic informational and psychological influences. Results: taking into account the provisions of the security strategies of Ukraine for 2020-2021, as well as scientific, practical information and international experience, separate approaches to the organization of media education have been summarized. It is emphasized that the person of the new era has become dependent on information. It must adapt to new challenges and risks generated by the media every day. Without knowing how to do this without harming yourself, it is easy to get lost. The result of the chaotic accumulation of various information, in which it is not clear what is important and what is not, where is the truth, and where is fiction and falsehood, is the loss of a sense of the world, the transformation of value orientations. And all this is a profitable platform for manipulation. A review was made of the Concept of the introduction of media education in Ukraine, approved by the Presidium of the National Academy of Pedagogical Sciences of Ukraine on April 21, 2016. Defined specific of a person’s media culture, media awareness, media literacy, media competence and media information literacy as factors that ensure a person’s informational armament are determined. Discussion: proper media culture of a person, media awareness, media literacy, media competence, media information literacy are important factors that ensure informational armament (spiritual, intellectual, moral, ethical, political), under which no informational influences on them are able to cause destructive thoughts and actions that lead to negative deviations on the path of sustainable progressive development of the named subjects, and this, in turn, is a guarantee of information security of the state.